AUTOSAR Communication Stack Implementation With FlexRay - Jansson, Jesper; Elgered, Johan (Chalmers tekniska högskola / Institutionen för data- och informationsteknik, Nätverk och system (Chalmers), 2011)
The demand for a high level of fault-tolerance and high bandwidth communication has increased, as a result of a growing number of ECU’s (Electronic Control Unit) inside vehicles. FlexRay was developed to meet the continuously growing demands, offering a time-triggered functionality and a higher bandwidth than existing protocols. To facilitate ECU software development, a group of automobile manufacturers, suppliers and tool developers created the standardized automobile software, AUTOSAR (Automotive Open System Architecture). Merging FlexRay and AUTOSAR together creates a new challenge for the automobile industry. By combining a faster and more reliable protocol with a standardized automotive E/E (Electrics/Electronics) architecture, manufacturers hope to meet future demands. The goals with this project were fulfilled with wide margin. In order to obtain a working AUTOSAR communication stack with FlexRay, the FlexRay Interface module was developed according to the AUTOSAR specifications. The new FlexRay Interface module together with the available FlexRay Driver module was integrated into the Arctic Studio environment. This proved that modules of different AUTOSAR versions are compliant with each other and that modules from different vendors can be combined. Also, tests with a developed demonstrator indicated that the FlexRay communication stack is fully functional regarding PDU (Protocol Data Unit) handling. The demonstrator showed that PDU transmissions and receptions were successful, i.e. no messages were lost, and that all time properties were fulfilled. The configuration of the different AUTOSAR modules were made with the Arctic Core configurator in the Arctic Studio, and a new FlexRay configurator adapted to the existing FlexRay modules.